آراءُ الأخفش الأوسط الصرفية والنحوية في كتاب ارتشاف الضرب لأبي حيان الأندلسي: دراسة وصفية تحليلية - Mohammad Adnan Rejab Al-Attar
Hayyan towards Al Akhfash Alawast. The research is important because it discusses the opinions of Al Akhfash Alawast in both syntax and declension fields and gathers them with classification. It also processes and describes the opinions’ content with their origins according to the syntactic requirements in Arabic language. The research follows the descriptive analytical approach، and it depends on specialized educational classification to the study of research، which stands for classifying syntactic issues to issues related to the shape of noun، verb and every topic or thesis related to them and organizing syntactic issues according to their declension cases. The sample of research was chosen and analyzed by a complete survey and exploring Al Akhfashe’s syntactic opinions and extrapolating them in the book “Getting the Example” or (irtishaf Al Darb). They reached more than four hundred issues classified according to the syntax and declension. The researcher has used the descriptive approach because he depended on a text by Al Akhfash proved by Abi Hayyan and quoted the talks of the scholars of Arabic language for analysis. The researcher also focused on the quotations and practical representations to the syntactic issues، which was got into consideration by Al Akhfash. Moreover, he concentrated on the attitude of Abi Hayyan and classifying them into agreed، disagreed and no opinion. Some of the expected results are the crucial role of Al Akhfash’s opinions in the Arabic syntax and declension fields، and the deep logical presentation of the syntactic opinions of Al Akhfash. The analyses and comments by Abu Hayyan increased the efficiency of Al Akfash’s ideas. Al Akhfash has employed the description and standard factors to control the word building، structures and sentences in Arabic language. That indicates the power of Al Akhfash’s syntactic interpretation in what is related to declension issues. The research also shows new welcoming horizons for dealing with word building in Arabic speech and its structures in modern Arabic approach.